Infografis Dampak Pandemi Covid-19 sebagai Upaya Edukasi Pemberdayaan Masyarakat Desa Katonsari Kecamatan Demak - Prizka Rismawati Arum; Eko Andy Purnomo; Ali Imron; M. Al Haris; Fatkhurrokhman Fauzi; Ach Ridoi Alambara (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2022)
Based on observations in the Katonsari Village, Demak District, Demak Regency, the delivery of information about Covid-19 and its impacts is still traditional, namely using text, tables or diagrams that are less attractive. Katonsari Village apparatus must have innovations in conveying information about Covid-19 and its impacts, such as new methods or media for conveying information. One of them is through infographics. Through the training, mentoring, mentoring and coaching that will be carried out, it is hoped that it will be able to make the officials of Katonsari Village, Demak District, Demak Regency more professional in utilizing IT to convey information on the impact of Covid-19 to the public through infographics. So that it can increase the awareness of the people of Katonsari Village in preventing Covid-19. This program consists of several stages which include delivering conceptual material on infographics, compiling data on the impact of Covid-19 into IT-based information, especially infographics, and socializing the results of infographics to the public.